Health service provision for disease control among prisoners: a conceptual note - Behnam Farhoudi; SeyedAhmad SeyedAlinaghi; Omid Dadras; Mehrzad Tashakoriyan; Mohammad Nazari Pouya; Mohammad Mehdi Gouya; Kate Dolan (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The aim of present study was to integrate vital noncommunicable diseases (coronary artery disease, hypertension, diabetes mellitus and mental health disorders) into Prison-Based Active Health Services Provision (PAHSP). Design/methodology/approach - On Jan 1, 2018, there were 230,000 prisoners in Iran. Timely and systematic detection and diagnosis of chronic health conditions among this population are imperative. The collaboration between healthcare providers in prison and members of the multidisciplinary team of the healthcare community outside prison initiated an active health service provision approach for HIV and tuberculosis (TB). Guidelines for the control of HIV and TB in prison were piloted, and the finalized version was named "Prison-based Active Health Services Provision" (PAHSP), which has been scaled up in 16 of 260 Iranian prisons. Finding - The PAHSP approach emphasizes the importance of early identification of key symptoms and risk factors. This approach provides an opportunity for improved prevention and treatment, enabling prisoners identified at risk or those who have been diagnosed with a target disease to be followed up and receive the appropriate health care. Originality/value - Initiatives such as screening for chronic health conditions coupled with treatment will reduce the burden of chronic illness among prisoners and the broader community, thereby saving on healthcare costs and lives.